IMPLEMENTASI METODE KRITIK INTRINSIK DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN - Shobah Shofariyani Iryanti; Fitriliza Fitriliza (Universitas Muhammadiyah Prof Dr Hamka, 2019)
Muhammadiyah 1 junior high school Depok hold a tadarus to read the Koran every Friday. However, the method applied is not appropriate and not right with the interests of students. Even students do not understand the various methods of reading the Koran. This is where researchers apply the intrinsic criticism method with the Al-Muyassar approach to improve the ability to read the Qur'an in this student of Muhammadiyah 1 junior high school Depok. This type of research is descriptive qualitative. Data collected includes primary data. And the study population was all students of the Muhammadiyah 1 junior high school Depok of grade eight . Data analysis in this study was observed by students and students of Muhammadiyah 1 junior high school Depok. And the results of this study will be used as a reference to implement the method of reading Almuyassar's intrinsic criticism in the Muhammadiyah 1 junior high school Depok.